2013
DOI: 10.1371/journal.pone.0083811
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Autoimmune-Associated Variants Confer Decreased IL-2R Signaling in CD4+CD25hi T Cells of Type 1 Diabetic and Multiple Sclerosis Patients

Abstract: IL-2 receptor (IL-2R) signaling is essential for optimal stability and function of CD4+CD25hiFOXP3+ regulatory T cells (Treg); a cell type that plays an integral role in maintaining tolerance. Thus, we hypothesized that decreased response to IL-2 may be a common phenotype of subjects who have autoimmune diseases associated with variants in the IL2RA locus, including T1D and MS, particularly in cells expressing the high affinity IL-2R alpha chain (IL-2RA or CD25). To examine this question we used phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
87
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 41 publications
10
87
3
2
Order By: Relevance
“…Several studies in autoimmune patients have reported that even modest changes in CD25 expression modify IL-2 sensitivity and greatly influence Treg function (26,27). In the present study we observed diminished CD25 expression, reduced sensitivity to low concentrations of IL-2, and increased cell apoptosis in Tregs from transplant recipients receiving tacrolimus therapy.…”
Section: Discussionsupporting
confidence: 64%
“…Several studies in autoimmune patients have reported that even modest changes in CD25 expression modify IL-2 sensitivity and greatly influence Treg function (26,27). In the present study we observed diminished CD25 expression, reduced sensitivity to low concentrations of IL-2, and increased cell apoptosis in Tregs from transplant recipients receiving tacrolimus therapy.…”
Section: Discussionsupporting
confidence: 64%
“…This emphasises the need for surveying the most complete set of variants possible in order to make cross disease comparisons. Variants in this region have previously been linked to several aspects of IL-2R signalling in T1D and MS patients [27] and the MS-associated variants we identify (whether under the M1 or M2 models) all showed some evidence of association with expression of CD25 on the surface of T cells, linking IL2RA in a primary way into the etiology of this disease. For T1D, we were only able to link the IL2RA intron 1 signal, shared with MS under the M1 model, to CD25 expression on memory T cells.…”
Section: Discussionmentioning
confidence: 61%
“…Horizontal bars represent means, with SD as error bars; statistical analysis between Tregs and Tconvs by one-way ANOVA with Sidák multiple comparisons test. ****P # 0.0001. with changes in Treg function (24)(25)(26)(27)(28)(29), so future studies to correlate changes in the Treg signature with genetic risk factors are warranted.…”
Section: Discussionmentioning
confidence: 99%